Comparative mathematical analysis of economically important ampelographic indicators in white wine vine varieties (Vitis vinifera L.) - Roychev, Venelin; Keranova, Neli (Acta Biologica Szegediensis, 2023)
A comparative mathematical analysis of economically important ampelographic indicators was performed in 32 local, introduced and newly bred white wine vine varieties. It was found that depending on the similarity and remoteness of the values of the studied indicators, the varieties are grouped into three generalized clusters. In the first, the varieties are characterized by a longer budding period and relatively lower productivity. In the second, they have similarities in the length of the budding period, long period of budding - technological maturity, moderate productivity, and close content of volatile acids in the wine. In the third, the newly bred two varieties Gergana and Misket Markovski, which are the most fertile and productive and with the smallest number of seeds in the berries. There is a high variability of the individual white wine varieties according to the studied economically valuable indicators. The indicators of bunch length and average weight per 100 berries have a stronger direct effect on the formation of the yield in individual varieties, and the average bunch weight, bunch width, percentage of mesocarp in berries, berry length and width, as well as the theoretical yield significantly affect indirectly the productivity of vines.